Associations between plant and pollinator communities under grassland restoration respond mainly to landscape connectivity. Issue 6 (25th July 2018) - Rotchés‐Ribalta, Roser; Winsa, Marie; Roberts, Stuart P. M.; Öckinger, Erik
Abstract: Land‐use change can disrupt associations between different trophic groups, but it is unclear if habitat restoration can recover these associations. In Sweden, restoration efforts have been applied to increase areas of semi‐natural grassland previously remaining as small fragments due to abandonment. We assessed how the associations between plant and pollinator communities can be modified by grassland abandonment and restoration, together with landscape connectivity. We surveyed plant, hoverfly and bee communities in 10 abandoned, 18 restored and 10 intact grasslands in south‐central Sweden, distributed along a gradient of isolation from other species‐rich grasslands. We assessed the effects of management history and connectivity on the relationships between several measures of the composition of plant and pollinator communities as well as between plant community composition and pollinator guilds. The composition of the local flowering plant community was an important determinant of both hoverfly and bee communities. However, plant‐pollinator associations were modulated by landscape connectivity and, to some extent, by grassland management history. Abundance, species richness and functional richness of bees and species richness of hoverflies were positively associated with local plant communities in isolated grasslands, but these associations weakened in well‐connected grasslands. In contrast, hoverfly abundance correlated positively with plant communities in well‐connected grasslands. The response of pollinator feeding guilds was consistent with overall pollinator communities. However, abundance of bees adapted to foraging on particular plants (long‐tongued and short‐tongued) responded positively to specific host plant species abundance. Synthesis and applications . Our results show how land use and landscape context can significantly affect interactions between different trophic levels. Land use and landscape context should therefore be recognised in grassland restoration guidelines. Enhancement of both functional‐rich and species‐rich plant communities, as well as increasing abundance and species and functional richness of host plants for specialist pollinators will amend pollinator diversity. Restoration actions should consider the spatial configuration of the landscape to improve its outcome. Efforts in more isolated grasslands should focus on promoting local habitat quality while, in more connected grasslands, the priority should be maintaining connectivity to well‐preserved grasslands. Abstract : Our results show how land use and landscape context can significantly affect interactions between different trophic levels. Land use and landscape context should therefore be recognised in grassland restoration guidelines. Enhancement of both functional‐rich and species‐rich plant communities, as well as increasing abundance and species and functional richness of host plants for specialist pollinators will amend pollinator diversity. Restoration actions should consider the spatial configuration of the landscape to improve its outcome. Efforts in more isolated grasslands should focus on promoting local habitat quality while, in more connected grasslands, the priority should be maintaining connectivity to well‐preserved grasslands.